The Expression of Symbolism and Philosophical Views in the Stories of Ulugbek Hamdam - Norova, Hilola (TLEP – International Journal of Multidiscipline, 2025)
This article discusses the symbolism and philosophical views of the author based on the analysis of  Ulugbek Hamdam's stories. The way of depicting the worldview and inner experiences of the characters in Ulugbek Hamdam's stories such as "A Cup of Water", "Journey",  " It's okay, you're in my life" is unique. Each word and meaning is aimed at revealing the inner world of the character. This article presents the analysis of the writer's symbolic and philosophical views, which are reflected in the skill of creating characters through the study of the above stories.